SOCIAL AND CULTURAL OF CRITICISM: (CONTRIBUTION TO THE INTERPRETATION OF THE TWELVE BOOKS OF SERBIAN LITERARU CRITICISM) (Heritage, 2022)
The paper sheds light on the importance of the first edition project of twelve volumes of Serbian literary criticism as a stage in the development of criticism as a culture in Serbian society and as a premise for the publication of a new edition of twenty-five volumes of literary criticism in which philosophers are included. Predrag Palavestra was at the center of the project, as the creator and implementer. In both editions, all the conditions and causes for the creation of his „History of Serbian Literary Criticism 1876 – 2007” as a fundamental book of Serbian science of literature and culture were collected.Palavestra came to all his findings, which are the foundation of Serbian literary criticism and culture, gradually, creating a large scientific project on literary criticism. On that road, the edition of twelve volumes of criticism was the first stage.
Keywords: literary criticism, literary history, Predrag Palavestra, Serbian culture, heritage, value